Artificial Intelligence as an Entry Point to Achieve Sustainable Development in the Business Environment in Accordance With the Pillars of the Kingdom’s Vision 2030 - Al-Anazi, Thamer Attih Sber (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to analyze the role of artificial intelligence as an entrance to achieving sustainable development in the business environment in accordance with the pillars of the Kingdom’s Vision 2030. To achieve this goal, the study followed the inductive approach, through a systematic review of previous studies that dealt with the subject of artificial intelligence in the business environment to achieve sustainable development, and the number of studies (20) studies. Among the most important findings of the study, the applications of artificial intelligence have proven their effectiveness in improving and developing the business environment, as they contributed to reducing time and effort and developing solutions to complex and difficult problems. It is one of the developed countries that have adopted the approach of artificial intelligence as an approach to achieving sustainable development in the business environment, and that the Kingdom of Saudi Arabia is one of the first Arab countries in the global index of artificial intelligence, which has contributed to reviving the economic situation of the Kingdom, and that the pillars of the Kingdom’s vision 2030 is keen to keep pace with modern trends In the applications of artificial intelligence to achieve sustainable development in the Saudi business environment, there are high expectations that artificial intelligence will improve the sustainability of economic growth.